Franz Kafka e o medium Kaiserpanorama - dos Santos, Thiago Benites (Contingentia, 2010)
The reception of Franz Kafka’s work is normally seen from the perspective of human condition, the labyrinth, the bureaucracy that imposes itself over the individual and so on. There is no doubt about the importance of this perspective for the study of Kafka’s work. Nevertheless, the objective of the present paper is to point out another aspect in Kafka’s work, which is the relation to the visual medium Kaiserpanorama in his fictional writings. The starting points of this discussion are the books “Kafka goes to the movies” by Hanns Zischler published in 1996 and “Kafka und der Film: über kinematographisches Erzählen” by Peter-André Alt published in 2009. Thus, based on these publications this study intends to analyse the importance, that this optical medium may have had over Franz Kafka and in which ways it is possible to identify this new perception in his literary work, specially in the tale “An imperial message”. The main topic is constructed around the profundity of the 3D-image as seen through a Kaiserpanorama, and its statical plasticity.